2001
DOI: 10.1016/s0304-3959(01)00282-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of sleep and its daily relationship to pain intensity in hospitalized adult burn patients

Abstract: Sleep disturbances are frequently reported in victims following burn injuries. This prospective study was designed to assess sleep quality and to examine its daily relationship to pain intensity within the first week of hospitalization. Twenty-eight non-ventilated patients were interviewed during 5 consecutive mornings (number of observations=140) to collect information about perceived quality of sleep (visual analogue scale, number of hours, number of awakenings, presence of nightmares). Pain intensity was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
122
5
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(141 citation statements)
references
References 46 publications
10
122
5
4
Order By: Relevance
“…Furthermore, while we were able to control for premorbid pain, health and mental health status, premorbid insomnia symptoms were not measured and so it remains possible that premorbid insomnia is also an important risk factor for developing chronic pain after acute injury. In support of this possibility, Raymond and colleagues have reported that retrospective ratings of pre-burn sleep problems predicted more intense pain during burn care procedures, more pain during the night, and more pain upon awakenings in hospitalized burn patients (41).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, while we were able to control for premorbid pain, health and mental health status, premorbid insomnia symptoms were not measured and so it remains possible that premorbid insomnia is also an important risk factor for developing chronic pain after acute injury. In support of this possibility, Raymond and colleagues have reported that retrospective ratings of pre-burn sleep problems predicted more intense pain during burn care procedures, more pain during the night, and more pain upon awakenings in hospitalized burn patients (41).…”
Section: Discussionmentioning
confidence: 98%
“…18 In clinical practice, patients frequently attribute their sleep disturbance to pain and pain intensity scores have been found to predict sleep disturbances. 19,20 Two long-term prospective studies have suggested that prolonged nighttime awakenings in patients with rheumatoid arthritis are associated with increased joint pain severity, and that subjective sleep problems increased risk for development of widespread pain within 15 mo in the general population. 21,22 Different theories have been advanced to explain the mechanisms underlying sleep and pain, including repeated mircroarousals and disruption of restorative slow-wave sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Raymond et al (13) investigated inpatients with burn injuries. The subjective quality of night sleep was a significant predictor for pain intensity on the following day.…”
Section: The Relationship Between Sleep and Pain As Suggested By Corrmentioning
confidence: 99%